2016
DOI: 10.1007/978-3-319-33111-9_21
|View full text |Cite
|
Sign up to set email alerts
|

Customer Reviews Analysis Based on Information Extraction Approaches

Abstract: Part 5: Languages and OntologiesInternational audienceThe existing information extraction approaches are generally analyzed and then categorized into several groups based on the superiority and the intelligence of the approaches as well as their capability to solve complex problems. Two practical approaches are provided to clarify how to use the information extraction solutions to obtain the valuable information from numerous reviews. The first approach is to support the front-end services in the EASY-IMP proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Recently, information retrieval, NLP, web semantics and text mining techniques have been attracting more attention from academics and industrialists who are challenged by the increasing size of textual data that needs to be collected, stored, analysed and managed in a PLM software application. Relevant research studies, including, but not limited to, Madhusudanan et al (2016), Jones et al (2016) and Zhang et al (2016) presented at the last PLM 2015 international conference -or Feldhusen et al (2012) have demonstrated the benefits of applying such bodies of knowledge to solve PLM problems. This section gives a broader literature review of the current existing solutions to not only extract textual requirements from prescriptive documents, but also classify them into disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, information retrieval, NLP, web semantics and text mining techniques have been attracting more attention from academics and industrialists who are challenged by the increasing size of textual data that needs to be collected, stored, analysed and managed in a PLM software application. Relevant research studies, including, but not limited to, Madhusudanan et al (2016), Jones et al (2016) and Zhang et al (2016) presented at the last PLM 2015 international conference -or Feldhusen et al (2012) have demonstrated the benefits of applying such bodies of knowledge to solve PLM problems. This section gives a broader literature review of the current existing solutions to not only extract textual requirements from prescriptive documents, but also classify them into disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relevant research studies, including, but not limited to, Madhusudanan et al (2016), Jones et al (2016) and Zhang et al (2016) presented at the last PLM 2015 international conference -or Feldhusen et al (2012) have demonstrated the benefits of applying such bodies of knowledge to solve PLM problems. This section gives a broader literature review of the current existing solutions to not only extract textual requirements from prescriptive documents, but also classify them into disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%